(3JaSjQ GdCOhjI GdeaQOIs
(3ChdgG (B:s
(3GdMeO ddg agPg ebOeI ai TQM CSeGA GdCOhjI GdeaQOI GdJi jMJGL EdjgG ai JQcjH GdCOhjI Ydi MQha GdeYLe s
(3BNQgG (B:s
(3jQGSjY gh GdGSajOGL , hgh eGYaf ef GdQUGU GdCShO HGdNd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B42 - (3U(B66s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B61 s
(3eUOQ GbJfGA GdCUd (B:s
(3TgjO Ydi (B(4/2112) s
Keywords: (3GdWHs